2022
DOI: 10.3390/ijms23169199
|View full text |Cite
|
Sign up to set email alerts
|

Oxidised Low-Density Lipoprotein-Induced Platelet Hyperactivity—Receptors and Signalling Mechanisms

Abstract: Dyslipidaemia leads to proatherogenic oxidative lipid stress that promotes vascular inflammation and thrombosis, the pathologies that underpin myocardial infarction, stroke, and deep vein thrombosis. These prothrombotic states are driven, at least in part, by platelet hyperactivity, and they are concurrent with the appearancxe of oxidatively modified low-density lipoproteins (LDL) in the circulation. Modified LDL are heterogenous in nature but, in a general sense, constitute a prototype circulating transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 154 publications
0
16
0
Order By: Relevance
“…However, several functions of these oxLDL receptors are still elusive. 129 Nevertheless, CD36 appears as a valuable target which warrants further investigations in the field of platelet biology.…”
Section: Discussionmentioning
confidence: 99%
“…However, several functions of these oxLDL receptors are still elusive. 129 Nevertheless, CD36 appears as a valuable target which warrants further investigations in the field of platelet biology.…”
Section: Discussionmentioning
confidence: 99%
“…If the lipid peroxidation process continues, LDL molecules could become highly oxidized to trigger macrophages activation and apoptosis [ 77 , 78 , 79 ]. Their main implication in pathological mechanisms remains the atherogenic processes, with no exception for ischemic stroke in which oxidized LDL is produced by a vicious cycle consisting of ROS production by the oxidized LDL-activated platelets [ 80 , 81 , 82 ].…”
Section: Lipid Peroxidationmentioning
confidence: 99%
“…It has been shown that oxLDL can interfere with cardinal platelet function such as adhesion [ 95 , 96 , 97 , 98 ], secretion [ 19 , 95 , 99 , 100 , 101 ], ROS generation [ 20 , 21 , 97 ], and microvesicles release, triggering a procoagulant phenotype with phosphatidylserine exposure [ 102 ], by acting synergistically with agonists, aggregation [ 103 , 104 , 105 ] even if, in other in vitro studies, low oxLDL levels seem attenuate platelet function and aggregation [ 106 , 107 , 108 , 109 ]. These contradictory findings could depend on the heterogeneous nature of oxLDL, such as the oxidized domain and extent of oxidation [ 110 ]. Actually, in vitro experiments demonstrate that the same LDL sample differently oxidized produces different products with distinct functional responses [ 111 , 112 , 113 ].…”
Section: Platelet Reactivity In Dyslipidemiamentioning
confidence: 99%
“…Conversely, CD36 is present on the plasma membrane both in resting and activated platelets. LOX-1 differs from CD36 also in binding oxLDL because it recognizes both mildly oxidized phospholipids and delipidated oxLDL [ 110 ]. Once on the platelet surface, LOX-1 is able to bind electronegative LDL driving the stimulation of signalling events including PI3K and MAPK/JNK which increase of p-selectin and GPIIb/IIIa expression [ 110 ].…”
Section: Role Of Scavenger Receptors In the Oxldl-induced Signalling ...mentioning
confidence: 99%
See 1 more Smart Citation